Performance analysis of the pull start in luge: integrated and real-time use of video and force measurement technologies - Stergiou, P.; Katz, L. (University of Calgary, 2010)
A good start in sport of Luge is understood, by the athletes and coach, as a start that produces maximal velocity of the sled with a trajectory that is symmetrical (right to left symmetry) off the handles. Video and force measurement systems have been used to offer the coach and athlete feedback on the kinematics (geometry of motion) and kinetics (external reaction forces). The co-ordination of these two technologies into one real-time feedback system have provided much of the necessary information for the assessment and correction in technique.